Getting institutions “Right” for whom? Credit constraints and the impact of property rights on the quantity and composition of investment - Carter, Michael R.; Olinto, Pedro (Wiley, 2003)
Property rights reform is typically hypothesized to boost investment through investment demand and credit supply effects. Yet when the credit supply effect is muted, property rights reform would be expected to induce liquidity‐constrained farms to reduce investment in movable capital even as they increase investment in attached capital. This expectation is corroborated by econometric analysis of panel data from Paraguay. While all farmers experience a positive investment demand effect, liquidity‐constrained producers correspondingly reduce their demand for movable capital. Given an estimated pattern of wealth‐biased liquidity constraints, property rights reform will get institutions “right” for only wealthier producers.